Advanced cueing of auditory stimulus to the head induces body sway in the direction opposite to the stimulus site during quiet stance in male participants - Hamada, Naoki; Kunimura, Hiroshi; Matsuoka, Masakazu; Oda, Hitoshi; Hiraoka, Koichi (Frontiers in Human Neuroscience, 2022)
Under certain conditions, tactile stimulus to the head induces movement of the head away from the stimulus, and this is thought to be caused by a defense mechanism. In this study, we tested our hypothesis that predicting the stimulus site of the head in a quiet stance activates the defense mechanism, causing a body sway to keep the head away from the stimulus. Fourteen healthy males aged 31.2 ± 6.8 years participated in this study. A visual cue predicting the forthcoming stimulus site (forehead, left side of the head, right side of the head, or back of the head) was given. Four seconds after this cue, an auditory or electrical tactile stimulus was given at the site predicted by the cue. The cue predicting the tactile stimulus site of the head did not induce a body sway. The cue predicting the auditory stimulus to the back of the head induced a forward body sway, and the cue predicting the stimulus to the forehead induced a backward body sway. The cue predicting the auditory stimulus to the left side of the head induced a rightward body sway, and the cue predicting the stimulus to the right side of the head induced a leftward body sway. These findings support our hypothesis that predicting the auditory stimulus site of the head induces a body sway in a quiet stance so as to keep the head away from the stimulus. The right gastrocnemius muscle contributes to the control of the body sway in the anterior-posterior axis related to this defense mechanism.